2002
DOI: 10.1677/jme.0.0280213
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of secreted frizzled-related protein 4 in decidual cells during pregnancy

Abstract: During pregnancy, the uterus shows marked morphological and physiological changes under the regulation of ovarian steroid. To elucidate the molecular cues of these changes, we tried to identify the transcripts differentially expressed in the pregnant rat uterus by using the suppression subtractive hybridization method. Seven independent clones were isolated and one of the up-regulated genes was secreted frizzled-related protein 4 (sFRP4). sFRP4 contains a Wnt-binding domain and belongs to the secreted frizzled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Similarly, James et al (36) found sFRP4 protein expression in human osteoarthritic articular cartilage coincided with the presence of terminal deoxynucleotidyl transferase-mediated nick end labeling-positive chondrocyte nuclei, suggesting a role for sFRP4 in chondrocyte apoptosis (36). On the other hand, sFRP4 mRNA expression was up-regulated in human endometrial carcinoma compared with normal endometrium (33), and, in the decidual cells of rats, sFRP4 expression correlates with the expression of proliferating cell nuclear antigen (37), suggesting a role in cellular proliferation. Despite abundant evidence for the role of Wnt signaling in development (8 -10), only one study has demonstrated sFRP4 expression in this process, i.e., in the developing murine lung (38).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, James et al (36) found sFRP4 protein expression in human osteoarthritic articular cartilage coincided with the presence of terminal deoxynucleotidyl transferase-mediated nick end labeling-positive chondrocyte nuclei, suggesting a role for sFRP4 in chondrocyte apoptosis (36). On the other hand, sFRP4 mRNA expression was up-regulated in human endometrial carcinoma compared with normal endometrium (33), and, in the decidual cells of rats, sFRP4 expression correlates with the expression of proliferating cell nuclear antigen (37), suggesting a role in cellular proliferation. Despite abundant evidence for the role of Wnt signaling in development (8 -10), only one study has demonstrated sFRP4 expression in this process, i.e., in the developing murine lung (38).…”
Section: Discussionmentioning
confidence: 93%
“…sFRP4 has been implicated in apoptosis (34 -36), proliferation (33,37), organ differentiation (38), and carcinogenesis (7,33,39). DDC-4, the rat homologue of sFRP4, was identified in involuted mammary glands, ovarian corpus luteum, and prostate, suggesting it is associated with apoptosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a clear deregulation of secreted frizzled related protein 4 (Sfrp4), a Wnt antagonist, is observed. This protein has been found to be differentially regulated in rodents, primates, and human myometrium (1,11,18,47). Upon implantation, Sfrp4 expression is restricted to the undifferentiated stromal cells forming a dividing zone between the circular muscle layer and the forming decidua.…”
Section: Microarray Analysis Ofmentioning
confidence: 99%
“…Quantitative reverse transcription-PCR (RT-PCR) studies done in our laboratory found that in postmenopausal women treated with estrogen for 3 months SFRP4 expression in the endometrium increased 9-fold. 1 SFRP4 expression levels are significantly decreased in endometrial cancer (26)(27)(28)(29). Downregulation of SFRP4 and associated promoter hypermethylation has been reported in several other cancers, including mesothelioma, chronic lymphocytic leukemia, and esophageal adenocarcinoma (30)(31)(32).…”
Section: Introductionmentioning
confidence: 97%